Strategi Pemasaran Digital Yang Efektif Untuk Meningkatkan Penjualan E-Commerce Fashion Di Indonesia Melalui Tiktok - Nur Fitri Eka Asbarini; Amriana Padlika; Dede Juanda (Jurnal Ekonomi dan Bisnis Digital, 2025)
Digital transformation has significantly reshaped marketing strategies, particularly in Indonesia's fashion e-commerce sector. TikTok has evolved into an effective marketing platform through interactive content and features such as TikTok Shop. This study employs a qualitative approach using literature review to analyze digital marketing strategies on TikTok. The findings indicate that authentic content, influencer collaborations, user-generated content, and multichannel strategies aligned with TikTok's algorithm contribute significantly to sales growth. These results offer strategic insights for fashion e-commerce businesses to optimize TikTok as a digital marketing channel.